2008
DOI: 10.3138/cpp.34.4.457
|View full text |Cite
|
Sign up to set email alerts
|

Overeducated Immigrants in the Canadian Labour Market: Evidence from the Workplace and Employee Survey

Abstract: Dans cet article, nous examinons la question de la surqualification des immigrants sur Ie marche du travail au Canada. Nous utilisons des donnees de 1999 tirees de I'Enquete sur Ie milieu de travail et les employes pour analyser les determinants de la surqualification et ses effets sur les revenus de travail. On trouve, dans la litterature actuelle, de nombreuses etudes sur les effets de la surqualification ; toutefois, celle-ci presente la premiere evaluation du rendement de I 'education au Canada realisee su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 18 publications
6
59
0
Order By: Relevance
“…More recent work from the United Kingdom also indicates that members of ethnic minorities are more likely to be overeducated (see Alpin, Shackleton and Walsh 1998), although there is heterogeneity among those minorities (see Battu and Sloane 2002). Th ere have been a number of studies examining returns to immigrants' education in the Canadian context (see Reitz 2001, Ferrer and Riddell 2008and Sweetman 2004), but to my knowledge only two studies have directly considered the impact of overeducation (see Galarneau andMorissette 2004 andWald andFang 2008). Th is lack of attention is somewhat surprising, given the prevalence of immigrant overeducation as described above, as well as the well-developed body of literature that examines the earnings consequences of overeducation (see McGuinness 2006 for an up-to-date and thorough review).…”
Section: Causes and Consequences: Overeducated Chinese Immigrants In mentioning
confidence: 99%
“…More recent work from the United Kingdom also indicates that members of ethnic minorities are more likely to be overeducated (see Alpin, Shackleton and Walsh 1998), although there is heterogeneity among those minorities (see Battu and Sloane 2002). Th ere have been a number of studies examining returns to immigrants' education in the Canadian context (see Reitz 2001, Ferrer and Riddell 2008and Sweetman 2004), but to my knowledge only two studies have directly considered the impact of overeducation (see Galarneau andMorissette 2004 andWald andFang 2008). Th is lack of attention is somewhat surprising, given the prevalence of immigrant overeducation as described above, as well as the well-developed body of literature that examines the earnings consequences of overeducation (see McGuinness 2006 for an up-to-date and thorough review).…”
Section: Causes and Consequences: Overeducated Chinese Immigrants In mentioning
confidence: 99%
“…Using census data, Galarneau and Morissette [6] �nd that 28% of recent immigrant males and 40% of corresponding females, each with a university degree, were in jobs with lower educational requirements compared, respectively, to 10% and 12% for Canadianborn workers. Wald and Fang [7] �nd that half of the immigrants into Canada who arrived between 1989 and 1997 were over-educated. ere is similar evidence from Europe: Nielsen [8] �nds that the incidence of over-education among Danish immigrants with foreign-acquired education was 47% compared with 33% among native Danes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have consistently found that recent immigrants continue to encounter significant barriers when searching for jobs in the labor market of their destination countries (Aydemir & Skuterud, 2005;Frenette & Morissette, 2005: Kahanec & Zaiceva, 2009Wald & Fang, 2009). Immigrant job search is a process of selecting different search methods that immigrants use to identify job opportunities and evaluate strategies for job success in their country of immigration (Greve, Salaff, & Chan, 2007).…”
Section: Introductionmentioning
confidence: 99%